Exploring reliability in information systems programmes - Denyer, David; Kutsch, Elmar; Lee-Kelley, Liz; Hall, Mark L. (Elsevier Science B.V., Amsterdam., 2011)
The recent epidemic of information systems (ISs) programme failures worldwide suggests that the effective management of programmes to cope with uncertainty and achieve mission in the medium term remains a key challenge. Research into high reliability organisations (HROs) has shown that it is possible to avoid, trap and mitigate the risks inherent in complex socio-technical systems. Studies of HROs originally focused on the operation of high risk technologies but have begun to explore other situations that present a similar need for reliable performance. One such environment is the IS programme. By comparing and contrasting the salient features of programme environments and HROs and presenting an in-depth case study with two embedded units of analysis (two troubled IS programmes), we aim to contribute to the ongoing debate about IS programme failure and to the theoretical development of programme reliability.